The Soviet military experience : a history of the Soviet Army, 1917-1991 - Reese, Roger R. (Warfare and history., 2000)
The Soviet Military Experience is the first general work to place the Soviet army into its true social, political and international contexts. It focuses on the Bolshevik Party's intention to create an army of a new type, whose aim was both to defend the people and propagate Marxist ideals to the rest of the world. It includes discussion of the:* origins of the Workers and Peasant's Red Army* effects of the Civil War* Bolshevik regime's use of the military as a school of socialism* effects of collectivization and rapid industrialisation of the 1920s and 1930s* Se.